2008
DOI: 10.1111/j.1745-3992.2008.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Putting Rubrics to the Test: The Effect of a Model, Criteria Generation, and Rubric‐Referenced Self‐Assessment on Elementary School Students' Writing

Abstract: The purpose of this study was to investigate the effect of reading a model written assignment, generating a list of criteria for the assignment, and self‐assessing according to a rubric, as well as gender, time spent writing, prior rubric use, and previous achievement on elementary school students' scores for a written assignment (N = 116). Participants were in grades 3 and 4. The treatment involved using a model paper to scaffold the process of generating a list of criteria for an effective story or essay, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
1
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(123 citation statements)
references
References 23 publications
7
106
1
9
Order By: Relevance
“…Their findings indicated that having students use model papers to generate criteria for a writing assignment and using a rubric to self-assess first drafts is positively related to the quality of their subsequent writing. Like Ross and his colleagues (1999), Andrade et al (2008) found that the improvements in students' writing included more effective handling of sophisticated qualities such as ideas and content, organization, and voice. When the findings of this study were translated into typical classroom grades, the average grade for the group that engaged in rubric-referenced self-assessment was a low B, but the average grade for the comparison group was a high C.…”
Section: Writingmentioning
confidence: 99%
See 3 more Smart Citations
“…Their findings indicated that having students use model papers to generate criteria for a writing assignment and using a rubric to self-assess first drafts is positively related to the quality of their subsequent writing. Like Ross and his colleagues (1999), Andrade et al (2008) found that the improvements in students' writing included more effective handling of sophisticated qualities such as ideas and content, organization, and voice. When the findings of this study were translated into typical classroom grades, the average grade for the group that engaged in rubric-referenced self-assessment was a low B, but the average grade for the comparison group was a high C.…”
Section: Writingmentioning
confidence: 99%
“…They noted that changes in conventions of language (sentence structure, grammar, and spelling) were negligible: The higher posttest scores of the weakest writers were the result of stronger performance on substantive criteria such as plot development, including the "integration of story elements around a central theme" and "the adoption of a narrative voice" (p. 124). Andrade et al (2008) also looked at the effectiveness of rubric-referenced self-assessment on scores on elementary school students' writing. Their findings indicated that having students use model papers to generate criteria for a writing assignment and using a rubric to self-assess first drafts is positively related to the quality of their subsequent writing.…”
Section: Writingmentioning
confidence: 99%
See 2 more Smart Citations
“…Research questions usually revolve around two main themes, which can be summarized as follows: (1) Is self assessment a reliable tool for assessing performance? (2) What are the variables likely to affect the reliability of scores, and how can these variables be controlled? The reliability of self assessment is usually measured by correlating the self-assessed performance score with that of the instructor or other external benchmarks (e.g., standardized tests).…”
Section: Literature Reviewmentioning
confidence: 99%